Exploring organizational career growth: a systematic literature review and future research directions - Limei Wang; Norhafizah Abu Hasan (Cogent Business & Management, 2024)
Organizational career growth (OCG) is important for the development of both individuals and organizations. Based on a systematic literature review (SLR) methodology that complies with PRISMA guidelines, this study synthesised 40 empirical articles on OCG published between 2013 and 2024. First, it summarised the characteristics of the articles on OCG research and addressed that the themes concerning OCG are concentrated in personal traits and work support, work emotions and work behaviours, and job performance and management practices. Then, the current research gaps were identified, and corresponding future research directions were proposed: to have more discussions on the mediating and interactive mechanisms of OCG, to pay more attention to the influencing factors at the organizational or cultural level, to focus on the potential negative impacts of OCG, and to further expand the theoretical perspectives on OCG. Finally, research implications are also provided.
Keywords: 650; Organizational career growth; systematic literature review; PRisMa; personal traits and work support; work emotions and work behaviours; job performance and management practices